ANALYSIS OF BUSINESS LICENSING IN THE DEVELOPMENT OF EIGER CAMP IN WEST BANDUNG REGENCY - Siagian, Afny Azzahra; Fauzi, Rizka Amanda; Haptoro, Dyanzah Aji; Wulandari, Wulandari; Satmaidi, Edra (jurnal.unprimdn.ac.id, 2025)
This study examines the spatial utilization compliance of the Eiger Camp Project located in Parongpong District, West Bandung Regency, which is situated within a water infiltration conservation zone as designated in the Regional Spatial Plan (RTRW). Although the developer claims to possess several permits, including the Environmental Impact Assessment (AMDAL), Building Approval (PBG), and site plan, the project was temporarily halted by local authorities due to the absence of a valid Spatial Utilization Activity Compliance (KKPR) document. Development in such conservation areas, which serve as water catchment and disaster-prone zones, raises both ecological and legal concerns. Using a normative-juridical approach, this research analyzes the relationship between the legality of permits and the substantive compliance with spatial zoning regulations as mandated by Indonesian law. The findings reveal that formal licensing, without alignment with RTRW zoning requirements, may result in legal violations and ecological degradation. Local governments play a vital role in monitoring and enforcing spatial planning policies; Thus, development in ecologically strategic areas must adhere to both legal and environmental considerations in a balanced manner.